Bta-miR-98 Suppresses Replication of Caprine Parainfluenza Virus Type 3 Through Inhibiting Apoptosis by Targeting Caspase-3 - Li, Jizong; Zhong, Chunyan; Liao, Zheng; Mao, Li; Li, Wenliang; Sun, Min; Liu, Maojun; Ji, Xinqin; Liu, Chuanmin; Xue, Tao; Yang, Leilei; Zhang, Wenwen (Frontiers in Immunology, 2020)
Caprine parainfluenza virus type 3 (CPIV3) is an emerging respiratory pathogen affecting the current sheep and goat industry in China and possibly worldwide. Accumulating evidence suggests that microRNAs play important roles in regulating virus-host interactions and can suppress or facilitate viral replication. In this study, we showed that CPIV3 infection induced apoptosis in Madin-Darby bovine kidney (MDBK) cells, as determined by morphological changes and flow cytometry. Caspase activity and the expression of pro-apoptotic genes further indicated that CPIV3 induced apoptosis by activating both the intrinsic and extrinsic pathways. We also demonstrated the involvement of bta-microRNA-98 (bta-miR-98) in regulating CPIV3-induced apoptosis. Bta-miR-98 was downregulated in MDBK cells infected with CPIV3. Overexpression of bta-miR-98 significantly decreased the activities of caspase-3, -8, and -9. Conversely, inhibition of bta-miR-98 had completely opposite effects. Furthermore, our data showed that bta-miR-98 markedly affected CPIV3 replication by regulating apoptosis. Importantly, we found that bta-miR-98 modulated CPIV3-induced apoptosis by targeting caspase-3, an effector of apoptosis. Collectively, our results may suggest that CPIV3 infection induced apoptosis, downregulated the levels of bta-miR-98, and this miRNA regulated viral replication through effected apoptosis. This study contributes to our understanding of the molecular mechanisms underlying CPIV3 pathogenesis.